2018
DOI: 10.1007/s40120-018-0101-4
|View full text |Cite
|
Sign up to set email alerts
|

Only Follow-Up of Memory B Cells Helps Monitor Rituximab Administration to Patients with Neuromyelitis Optica Spectrum Disorders

Abstract: In contrast to total CD19+ cell, detected with the routine technique, CD19+ CD27+ memory B cells are a reliable marker for biological relapse and allow a decrease in the frequency of infusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
(37 reference statements)
2
19
0
Order By: Relevance
“…Moreover, in contrast to total CD19+ cell detected with routine techniques, the addition of assessment of subpopulations of B cells using multicolor flow cytometry, namely CD19+ CD27+ memory B cells, have been shown to be a reliable marker that correlates with biological relapse. In this study, the authors found the reemergence of naïve B cells prior to the emergence of CD19+ CD27+ memory B cells in some cases, and that this reemergence did not correlate with total B cell emergence, allowing for a decrease in the frequency of rituximab infusions ( 81 ). Low dose rituximab regimens have been described by several groups ( 82 84 ), but notably, dosing may need to be more frequent with lower doses.…”
Section: Review Of Current Knowledgementioning
confidence: 83%
“…Moreover, in contrast to total CD19+ cell detected with routine techniques, the addition of assessment of subpopulations of B cells using multicolor flow cytometry, namely CD19+ CD27+ memory B cells, have been shown to be a reliable marker that correlates with biological relapse. In this study, the authors found the reemergence of naïve B cells prior to the emergence of CD19+ CD27+ memory B cells in some cases, and that this reemergence did not correlate with total B cell emergence, allowing for a decrease in the frequency of rituximab infusions ( 81 ). Low dose rituximab regimens have been described by several groups ( 82 84 ), but notably, dosing may need to be more frequent with lower doses.…”
Section: Review Of Current Knowledgementioning
confidence: 83%
“…Cluster B1 expressed naive B cells related genes ( CXCR4 , CD83 , and IGHD ) ( 15 ), and CD27 was expressed in clusters B2 and B6. Cluster B2 was similar to memory B cell ( 32 ), and cluster B6 expressed high levels of immunoglobulin genes ( IGHA1 , IGHG1 , and IGLC2 ), which defined them as plasma cells. Cluster B5 exhibited the expression of CLEC4C , GZMB , PTPRS , and IL3RA , which is similar to the phenotype of pDC-like cells ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, memory B cells were shown to worsen the severity of NMOSD [ 184 ]. In rituximab-treated NMOSD patients, elevated CD27 + memory B cells were reported to be a reliable marker for biological and clinical relapses after depletion [ 185 , 186 , 187 ]. In contrast, a depletion of memory B cells was associated with a clinical response to rituximab treatment [ 188 ].…”
Section: Ineffectiveness and Failure Of Ms Therapeutics In Nmosdmentioning
confidence: 99%